NOX reduction and efficiency improvements by means of the Double Fuel HCCI combustion of natural gas–gasoline mixtures. (5th June 2016) - Pipitone, Emiliano; Genchi, Giuseppe
Abstract: Homogeneous Charge Compression Ignition (HCCI) and Double Fuel (DF) combustion represent two innovative processes sharing a strong potential for pollutant emissions and fuel consumption reduction. HCCI regards the auto-ignition of a homogeneous premixed charge of air and fuel, featuring very low NOX emissions and good efficiency. Double Fuel (DF) instead indicates the simultaneous combustion of gasoline and natural gas (or gasoline and LPG), premixed with air by the port injection of both fuels within same engine cycle. Since fuel mixtures enhances the HCCI performances widening the range of possible operating conditions, the authors tested the HCCI combustion process using natural gas–gasoline mixtures on a CFR engine, endowed with two injection systems for the accurate control of both fuel mixture composition and overall air-to-fuels ratio. Stable and knock-free DF-HCCI combustions were obtained by combining different intake temperatures and compression ratios, in a range of engine load between 20% and 54% of the maximum load obtained with normal Spark Ignition (SI) operation. Noticeable increment of engine efficiency (+23%) and a strong reduction of pollutant emissions were found in comparison to SI operation, above all in terms of NOx, which was reduced by 2 order of magnitude.